2002
DOI: 10.1046/j.1432-1033.2002.03064.x
|View full text |Cite
|
Sign up to set email alerts
|

GNA33 from Neisseria meningitidis serogroup B encodes a membrane‐bound lytic transglycosylase (MltA)

Abstract: In a previous study, we used the genome of serogroup B Meningococcus to identify novel vaccine candidates. One of these molecules, GNA33, is well conserved among Meningococcus B strains, other Meningococcus serogroups and Gonococcus and induces bactericidal antibodies as a result of being a mimetic antigen of the PorA epitope P1.2. GNA33 encodes a 48‐kDa lipoprotein that is 34.5% identical with membrane‐bound lytic transglycosylase A (MltA) from Escherichia coli. In this study, we expressed GNA33, i.e. Meningo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Biochemical characterization of the recombinant protein, expressed and purified from E. coli, showed that GNA33 is able to degrade both insoluble murein sacculi and unsubstituted glycan strands. The results confirmed that GNA33 is a lytic transglycosylase with muramidase activity (Jennings et al, 2002). The recombinant protein elicits bactericidal antibody by mimicking a surface-exposed epitope of porin A (PorA) and confers passive protection against bacteremia in an infant rat model.…”
Section: Genome-based Approaches To Vaccines Discovery 23supporting
confidence: 64%
“…Biochemical characterization of the recombinant protein, expressed and purified from E. coli, showed that GNA33 is able to degrade both insoluble murein sacculi and unsubstituted glycan strands. The results confirmed that GNA33 is a lytic transglycosylase with muramidase activity (Jennings et al, 2002). The recombinant protein elicits bactericidal antibody by mimicking a surface-exposed epitope of porin A (PorA) and confers passive protection against bacteremia in an infant rat model.…”
Section: Genome-based Approaches To Vaccines Discovery 23supporting
confidence: 64%
“…In a different approach, also aimed at increasing expression of GNA33 in a secreted form, the sequence encoding the mature portion of GNA33 was fused in-frame with the signal peptide sequence from another N. meningitidis lipoprotein, NMB1946 (Jennings et al, 2002). Substitution of the GNA33 signal peptide sequence with that of NMB1946 was found to give a level of GNA33 comparable to that obtained for the 'native' clone expressed in the presence of pLysS.…”
Section: Resultsmentioning
confidence: 99%
“…GNA33 encodes a protein of 441 aa with an N-terminal 20 aa signal sequence and shares 34?5 % sequence identity with the E. coli membrane-bound lytic transglycosylase A (MltA) (Jennings et al, 2002). Recently, functional homology of GNA33 to E. coli MltA has been confirmed by in vitro characterization of its muramidase and lytic transglycosylase activity (Jennings et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Meningococcal PBP2 has been shown to interact with the lytic transglycosylase MltA (55). Furthermore, the E. coli homolog of meningococcal PBP2, PBP3, can form a complex with the lytic transglycosylase Slt70 and the low molecular weight PBP7/8 (56).…”
Section: Discussionmentioning
confidence: 99%